Back calculation Anti Windup PID controller on Several Well-Known Tuning Method for Glycerin Bleaching Process Temperature Regulation - A. Jalil, Mohd Hafiz; Taib, Mohd Nasir; Rahiman, M. H. Fazalul; Hamdan, Rohaiza (International Journal of Integrated Engineering, 2015)
The aim of this paper is to comprehend the performance of back calculation anti windup scheme with difference tracking time constant, Ta on Proportional – Integral - Derivative (PID) controller for improving temperature regulation of glycerin bleaching process. Several available well tuning methods including Ziegler Nichols (ZN), Internal Model Control (IMC) and Integral Square Error (ISE)-Load are used and analyzed. The performance of the controller tuning methods are compared based on percentage of overshoot, settling time, rise time and time to recovery on the presence of disturbance. From the results, the best performance of temperature regulation for glycerin bleaching process can be reached by using ISE-Load tuning with tracking time constant, Ta equal to derivative time constant, Td.